2014
DOI: 10.1038/srep06198
|View full text |Cite
|
Sign up to set email alerts
|

The vacuolar-sorting protein Snf7 is required for export of virulence determinants in members of the Cryptococcus neoformans complex.

Abstract: Fungal pathogenesis requires a number of extracellularly released virulence factors. Recent studies demonstrating that most fungal extracellular molecules lack secretory tags suggest that unconventional secretion mechanisms and fungal virulence are strictly connected. Proteins of the endosomal sorting complex required for transport (ESCRT) have been recently associated with polysaccharide export in the yeast-like human pathogen Cryptococcus neoformans. Snf7 is a key ESCRT operator required for unconventional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 83 publications
1
39
0
Order By: Relevance
“…We also note that a recent report by Godinho et al . () described an avirulent phenotype for a snf7 mutant of C. neoformans . Overall, we conclude that the ESCRT‐0, ‐I, ‐II and ‐III proteins are required for virulence in mice as well as survival in macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also note that a recent report by Godinho et al . () described an avirulent phenotype for a snf7 mutant of C. neoformans . Overall, we conclude that the ESCRT‐0, ‐I, ‐II and ‐III proteins are required for virulence in mice as well as survival in macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…However, a role for ESCRT proteins in the secretion of capsular material to influence capsule size is also possible, as suggested by Godinho et al . ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to use host iron sources, such as heme/hemoglobin and transferrin, is advantageous for the growth and survival of C. neoformans inside a vertebrate host (Jung et al, ). Previous studies have shown key roles for the ESCRT proteins Vps23, Vps22, and Snf7 in the use of heme iron and in the virulence of C. neoformans (Hu et al, ; Godinho et al, ; Hu et al, ). Additionally, a putative hemophore, Cig1, was discovered to be involved in heme binding and uptake and in virulence (Cadieux et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the extracellular molecules in fungi are secreted through non-canonical mechanisms that are regulated at multiple levels. Regulators of non-canonical secretion in fungi include Golgi reassembly and stacking protein (Grasp) [24], sucrose non-fermenting protein 7 (Snf7) [25], and the putative aminophospholipid translocase (flippase) Aptl [26]. …”
Section: Introductionmentioning
confidence: 99%